The dietary inflammatory index and its association with the prevalence of hypertension: A cross-sectional study - Zhou, Nan; Xie, Zhi-Ping; Liu, Qing; Xu, Yun; Dai, Si-Cheng; Lu, Juan; Weng, Jia-Yi; Wu, Li-Da (Frontiers in Immunology, 2023)
Aims: We aim to investigate the association of dietary inflammation index (DII) with the prevalence of hypertension in a large multiracial population in the U.S. Methods: Participants from the National Health and Nutrition Examination Survey (NHANES) (1999–2018) were enrolled in the present cross-sectional study. Dietary information was obtained and used to calculate DII, blood pressures of participants were measured by experienced examiners. NHANES survey was conducted using the method of “Stratified multistage probability sampling” and this is a weighted analysis followed NHANES analytic guidance. Baseline characteristics of participants with and without hypertension were compared in detail. We adopted weighted multivariable Logistic regression analysis to investigate the association of hypertension with DII. Lasso regression was carried out to screen out the most correlated dietary factors with hypertension risk. Moreover, nomogram model including the key dietary factors was established and the receiver operating characteristic (ROC) curve was used to evaluate the discriminatory power. Results: 45,023 participants were enrolled representing 191 million residents in the U.S. Participants with hypertension had an elevated DII comparing with those without hypertension. Results of Logistic regression demonstrated that the increment of DII was strongly associated with hypertension after adjusting for cofounding factors. Considering the application of medication can impact blood pressure, we excluded any participant received any drug treatment, and the results of sensitive analysis was consistent with main analysis. The nomogram model based on key dietary factors screened out by Lasso regression showed a favor discriminatory power with area under curve (AUC) of 78.5% (95% CI: 78.5% - 79.3%). Conclusion: DII is strongly associated with the incidence of hypertension. For better prevention and treatment of hypertension, more attention should be paid to controlling dietary inflammation.